JENIS DAN LAMA PENYIMPANAN DINGIN TERHADAP KARAKTERISTIK SURIMI DARI IKAN PATIN (P. hypophthalamus ) - Tridarmawan, Hidayat (Universitas Muhammadiyah Palembang, 2018)
ABSTRACT This study aims to determine the best surimi shelf life of catfish and to know the quality of catfish surimi. The chemical characteristics of catfish preserved in cold storage consisted of 11.47-11.80% protein content, moisture content of 70.67-75.94%, pH 6.83-7.18 and EMC (Expressible Moisture Content) 28 , 28-32.07%. The organoleptic characteristics of catfish surimi consisted by the prefered degree of the colors of 1,6-3, the prefered degree of the aroma of 2.55-3.2 and the prefered degree of texture -3.41 ? 3.41. The storage of catfish surimi in freezer storage for 3 days is the best storage treatment with chemical characteristics consisted of 11,77% protein value, moisture content 72,67%, pH 6,94 and EMC 29,04; Organoleptic characteristics consisted of the preferred degree of color 2.6 by preferred criteria, and for texture -0.71 by preferred criteria. During 9 days cold storage surimi catfish produced decreased quality indicated by the occurrence of decreased levels of protein, increase in water content, pH, and EMC